Implementation Of Laws On The Criminal Jurisdiction System Using A Restorative Justice Approach (A Case Study at ‘Aisyiyah Legal A id Institute, Central Java) - Zaenal Aripin (Law and Justice, 2020)
This article aims to determine the implementation of the juvenile criminal justice system law in upholding child criminal law in Surakarta, explain the process of assistance for victims and child offenders who are dealing with the law with a restorative justice approach in the form of diversion, and explain the obstacles found LBH (Legal Aid) 'Aisyiyah Central Java in law enforcement which acts as a child crime in Surakarta. This study uses an empirical approach. This research was conducted by examining primary data in the field, namely LBH Aisyiyah Central Java in the form of facts about the results of research directly at the research location and the results of interviews with members of advocacy organizations at LBH 'Aisyiyah, Central Java and in the Legal and Human Rights Council of' Aisyiyah Regional Leaders. Central Java and secondary data. The results showed that based on the results of the study in 10 criminal cases committed by children who were resolved by diversion in Surakarta, they had fulfilled and were in accordance with the Articles regulating diversion in the SPPA Law.  Whereas the concept of diversion has been running in Surakarta with many determinations of the results of a diversion agreement between the families of the victims and the families of the perpetrators and also LBH (Legal Aid) or related LSM (Non-Govermental Organization)  for crimes committed by minors. So that the application of the Law on Juvenile Criminal Justice System in law enforcement of child criminal acts has been running quite effectively.  Keywords: SPPA Law, diversion, restorative justice, Surakarta